Dissecting Incongruence between Concatenation- and Quartet-Based Approaches in Phylogenomic Data. (22nd February 2021) - Shen, Xing-Xing; Steenwyk, Jacob L; Rokas, Antonis
Abstract: Topological conflict or incongruence is widespread in phylogenomic data. Concatenation- and coalescent-based approaches often result in incongruent topologies, but the causes of this conflict can be difficult to characterize. We examined incongruence stemming from conflict the between likelihood-based signal (quantified by the difference in gene-wise log-likelihood score or $Δ $ GLS) and quartet-based topological signal (quantified by the difference in gene-wise quartet score or $Δ $ GQS) for every gene in three phylogenomic studies in animals, fungi, and plants, which were chosen because their concatenation-based IQ-TREE (T1) and quartet-based ASTRAL (T2) phylogenies are known to produce eight conflicting internal branches (bipartitions). By comparing the types of phylogenetic signal for all genes in these three data matrices, we found that 30–36% of genes in each data matrix are inconsistent, that is, each of these genes has a higher log-likelihood score for T1 versus T2 (i.e., $Δ $ GLS $>$ 0) whereas its T1 topology has lower quartet score than its T2 topology (i.e., $Δ $ GQS $<$ 0) or vice versa. Comparison of inconsistent and consistent genes using a variety of metrics (e.g., evolutionary rate, gene tree topology, distribution of branch lengths, hidden paralogy, and gene tree discordance) showed that inconsistent genes are more likely to recover neither T1 nor T2 and have higher levels of gene tree discordance than consistent genes. Simulation analyses demonstrate that the removal of inconsistent genes from data sets with low levels of incomplete lineage sorting (ILS) and low and medium levels of gene tree estimation error (GTEE) reduced incongruence and increased accuracy. In contrast, removal of inconsistent genes from data sets with medium and high ILS levels and high GTEE levels eliminated or extensively reduced incongruence, but the resulting congruent species phylogenies were not always topologically identical to the true species trees.[Conflict; gene tree; phylogenetic signal; phylogenetics; phylogenomics; Tree of Life.]